Solarizing deep tubewells for more reliable and sustainable irrigation in Nepal’s Terai region - Neupane, Nilpane; Shrestha, Shisher; Poudel, Prasis (CGIAR, 2024)
A NEXUS Gains analysis of deep wells in Nepal’s Terai region suggests that solarizing deep tube wells could lead to more reliable irrigation practices and reduce costs for farmers